Changes in physical activity and sedentary behaviours of children living in Italy due to the COVID-19 pandemic: the EPaS-ISS study - Paola Nardone; Serena Broccoli; Angela Spinelli; Marta Buoncristiano; Silvia Andreozzi; Mauro Bucciarelli; Marco Giustini; Silvia Ciardullo; on behalf of the EPaS-ISS Group (Archives of Public Health)
Abstract Background Most governments worldwide introduced containment measures to protect people from the risk of SARS-CoV-2 virus infection which also affected children. The COVID-19 pandemic and the resulting confinement at home may have affected physical health and mental well-being especially among vulnerable young people, widening health disparities. Therefore, the aim of the EPaSS-ISS study was to study the changes in physical activity and sedentary behaviours among 8–9 years old Italian students during the pandemic of COVID-19 compared with before the pandemic. Methods Data were collected using a web questionnaire. The target population was parents of children attending third-grade primary schools and living in Italy. A cluster sample design was used. Logistic regression models were used to explore changes between the pre-pandemic and pandemic periods in children’s studying hours, active play and screen time. The possible effects of gender, geographical area of residence, parents’ nationality and educational level, family structure, family-perceived wealth, availability of home outdoor spaces and house size were investigated. A stratification by sociodemographic characteristics of children and parents was also included in the analysis. Results 4863 children were included: 47.9% were females, the average age was 8 years and 9 months (SD ± 5 months). The parents reported that 44.3% of their children increased the time spent studying at home, 52.7% the screen time for non-educational purposes on weekdays, and 47.3% at weekends; 44% of the children decreased their time spent playing actively outside school hours on weekdays and 39.3% at weekends. A larger increase of sedentary lifestyle was found among children with at least one parent with a medium (OR:2.57; 95%CI:1.78–3.72) or high educational level (OR:3.32, 95%CI:2.29–4.82), with low family-perceived wealth (OR:1.21; 95%CI:1.03–1.41), with both Italian parents (OR:1.44; 95%CI:1.10–1.90), resident in Centre (OR:1.25; 95%CI:1.04–1.50) or South (OR:1.26; 95%CI:1.05–1.51) Italy. No outdoor spaces (OR:2.14; 95%CI:1.82–2.51) and home size < = 90m2 (OR:1.41; 95%CI:1.05–1.68) had also a negative effect on children’s behaviours. Conclusions In Italy physical activity decreased and sedentary behaviours increased among 8–9 years old children during the COVID 19 pandemic.